Political and Public Perceptions of Students’ Dressing Codes in Higher Learning Institutions - et.al, Mpawenimana Abdallah Saidi (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study sought to explore Politics of students’ dressing codes and its impact on political and public perceptions in Tanzanian higher learning institutions. It was a qualitative study which used an in depth interviews to collect data from 10 administrative regions (Mwanza, Arusha, Dodoma, Dar es salaam, Mbeya, Iringa, Kagera, Tanga, Mtwara and Tabora) in Tanzania. A total of 40 informants were purposefully selected to participate in the study meanwhile a thematic analysis was employed to analyse and manage the data. In order to produce indisputable data, indispensable cleanings, transcription, coding, organizing, and theming were ascertained in the process. The findings reveal that, there is negative perceptions towards students’ dressing codes which resulted into ethical based discontent amongst Tanzanians on the dressing codes of higher learning institutions’ students meanwhile public comments to the legislative bodies to make a law or related policy that will be implemented to regulate all kinds of undesirable dressing behavior in learning institutions.